Nutritional composition of gedi (Abelmoschus manihot) leaves powder in comparison to common natural galactagogue plants in Indonesia - GRACE MARLINA WINATA; HARDINSYAH HARDINSYAH; SRI ANNA MARLIYATI; RIMBAWAN RIMBAWAN; DIMAS ANDRIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Winata GM, Hardinsyah H, Marliyati SA, Rimbawan R, Andrianto D. 2024. Nutritional composition of gedi (Abelmoschus manihot) leaves powder in comparison to common natural galactagogue plants in Indonesia. Biodiversitas 25: 2583-2589. Galactagogue is a substance believed to help initiate, maintain, and increase breast milk production. Low or no breast milk production and perceived insufficient milk are the most common reasons that cause a mother to stop breastfeeding earlier. To help this problem, natural galactagogue consumption is highly recommended. Gedi (Abelmoschus manihot (L.) Medik) plant is locally used in Indonesia as food ingredient and medicinal plant. The leaves have been believed for generations to increase breast milk production. This study aimed to evaluate the macro- and micronutrient content of gedi leaves powder, compared to torbangun (Coleus amboinicus) and katuk (Sauropus androgynous) leaves powder as common natural galactagogue plants in Indonesia. Clean fresh leaves were oven-dried and ground. Carbohydrates, crude fiber, protein, fat, ash, energy, water, vitamins A, B1, B2, B6, B9, C, E, and K, mineral calcium, iron, magnesium, sodium, zinc, phosphorus, and potassium were analyzed using standard methods. The analysis result showed that gedi leaves powder contained highest carbohydrate (51%), crude fiber (10.3%), vitamin K (1,110 µg/100 g), mineral magnesium (700 mg/100 g), sodium (89.6 mg/100 g), and calcium (2,671 mg/100 g) content, which were significantly different compared to torbangun and katuk leaves powder (P<0.05). Total energy (344 kcal/100 g), protein (25%), ash (13.6%), zinc (4.8 mg/100 g), potassium (2,314 mg/100 g), and iron (8.9 mg/100 g) content of gedi leaves powder were between torbangun and katuk leaves powder. This study showed that gedi leaves powder had a high carbohydrate, crude fiber, vitamin K, and mineral, especially calcium and magnesium, and sufficient protein and energy content, compared to torbangun and katuk leaves powder as common natural galactagogue plants in Indonesia. Further research in the extraction, bioactive compound, and in vivo study has to be carried out to scientifically prove the galactagogue effects of gedi leaf powder.